The core element of a CpG island protects avian sarcoma and leukosis virus-derived vectors from transcriptional silencing - Šenigl, Filip; Plachý, Jiří; Hejnar, Jiří (Journal of virology, 2008)
Unmethylated CpG islands are known to keep adjacent promoters transcriptionally active. In the CpG island adjacent to the adenosine phosphoribosyltransferase gene, the protection against transcriptional silencing can be attributed to the short CpG-rich core element containing Sp1 binding sites. We report here the insertion of this CpG island core element, IE, into the long terminal repeat of a retroviral vector derived from Rous sarcoma virus, which normally suffers from progressive transcriptional silencing in mammalian cells. IE insertion into a specific position between enhancer and promoter sequences led to efficient protection of the integrated vector from silencing and gradual CpG methylation in rodent and human cells. Individual cell clones with IE-modified reporter vectors display high levels of reporter expression for a sustained period and without substantial variegation in the cell culture. The presence of Sp1 binding sites is important for the protective effect of IE, but at least some part of the entire antisilencing capacity is maintained in IE with mutated Sp1 sites. We suggest that this strategy of antisilencing protection by the CpG island core element may prove generally useful in retroviral vectors.
Keywords: Animals; Humans; biologické modely; vazebná místa; ptačí sarkom; lidé; financování organizované; zvířata; Flow Cytometry; Gene Silencing; Sp1 Transcription Factor; transkripční faktor Sp1; Terminal Repeat Sequences; Binding Sites; Rous sarcoma virus; Sarcoma, Avian; umlčování genů; mutace; Financing, Organized; průtoková cytometrie; virus Rousova sarkomu; reportérové geny; virus ptačí leukózy; Mutation; Avian Leukosis Virus; koncové repetice; Transcription, Genetic; Models, Biological; CpG Islands; genetická transkripce; CpG ostrůvky; Genes, Reporter